Extracurricular Educational Establishments of Artistic and Aesthetic Direction in Khmelnytskyi - Oliinyk, Nataliya (Pedagogical Discourse, 2013)
The place and role of extracurricular establishments in the contemporary educational activity are relieved. It is found out that school education is a component of continuing education students, which greatly affects the socialization of the individual, the disclosure of its creative potential, the formation of values ​​and moral orientations. The questions of school extracurricular educational establishments of aesthetic and artistic direction in Khmelnytsky are observed. Achievements and accomplishments of creative teams that exist in these institutions are demonstrated on concrete examples. The necessity of the existence of these institutions in the public education system in Ukraine is proved.